2010
DOI: 10.1097/fpc.0b013e328335b02d
|View full text |Cite
|
Sign up to set email alerts
|

HIV protease inhibitors are substrates for OATP1A2, OATP1B1 and OATP1B3 and lopinavir plasma concentrations are influenced by SLCO1B1 polymorphisms

Abstract: OATP1B1 and OATP1B3 are major hepatic drug transporters whilst OATP1A2 is mainly located in the brain but is also located in liver and several other organs. These transporters affect the distribution and clearance of many endo- and xenobiotics and have been reported to have functional SNPs. We have assessed the substrate specificites of these transporters for a panel of antiretrovirals and investigated the effects of SNPs within these transporters on the pharmacokinetics of lopinavir. SLCO1A2, SLCO1B1 and SLCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 50 publications
11
135
3
Order By: Relevance
“…34,35 In addition to the OATP1B inhibitory potential of HIV PI, several studies revealed that these drugs also show affinity for OATP1B isoforms as substrates. 19,20 Moreover, the 521T>C gene polymorphism in SLCO1B1 is significantly associated with higher lopinavir plasma concentrations. 20 These findings raise the question whether hepatic OATP isoforms play a pivotal role in the hepatic uptake of HIV PI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 In addition to the OATP1B inhibitory potential of HIV PI, several studies revealed that these drugs also show affinity for OATP1B isoforms as substrates. 19,20 Moreover, the 521T>C gene polymorphism in SLCO1B1 is significantly associated with higher lopinavir plasma concentrations. 20 These findings raise the question whether hepatic OATP isoforms play a pivotal role in the hepatic uptake of HIV PI.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Moreover, the 521T>C gene polymorphism in SLCO1B1 is significantly associated with higher lopinavir plasma concentrations. 20 These findings raise the question whether hepatic OATP isoforms play a pivotal role in the hepatic uptake of HIV PI. The aim of this study was to further investigate the exact role of hepatic uptake transport in the overall hepatic Cl of HIV PI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common SNP in the SLCO1B1 gene, 521T>C, has been associated with higher plasma levels of LPV [64][65][66][67], but the clinical significance is still uncertain and further studies are needed to confirm this association and to assess the impact on LPV pharmacokinetics.…”
Section: Pharmacogenetics Of Lopinavirmentioning
confidence: 99%
“…Compared with wild-type OATP1B1, c.521T>C was associated with increased systemic exposure to multiple drugs, including oral pravastatin [23,24] , fexofenadine [25] , and lopinavir [26,27] . In addition, the co-administration of OATP1B1 inhibitors may affect the pharmacokinetics of its substrates.…”
mentioning
confidence: 99%